School Culture as a Field of Analysis: Review of Research in Kazakhstan and Poland - Aleksandra Tłuściak-Deliowska; Urszula Dernowska; Aigerim Kosherbayeva (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The post-socialist political transformation after 1989 initiated several changes in the political, economic, and social spheres in many countries. Changes have also occurred in educational institutions, which have been transformed over the last three decades because of changes of the program and organizational nature. The actual scope and depth of changes taking place at school requires the isolation of a comprehensive construct that will allow to capture the features and changes taking place at various, also hidden, levels of school functioning. These criteria are best met by the concept of school culture. Research Aim: The aim was to analyze empirical Polish and Kazakh articles on school culture. Method: To find relevant literature, a search strategy was developed which consisted of several stages, including searching databases of peer-reviewed journal articles published in English, Kazakh and Polish in the last 30 years. Results: Although publications from the last 30 years were analyzed, there were not many publications that met the imposed analytical criteria. Considering Kazakh publications, it should be noted that the dominant approach is the quantitative one, however, there are no studies that address school culture issue directly. In the case of publications of authors dealing with the issue of school culture in Poland, the quantitative approach also dominates, but the authors refer directly to the category of school culture. Although publications in the native language dominate, the number of texts in English is increasing. Conclusions: The results showed considerable differences in the nature of the empirical discourse regarding school culture.